Akhlak Warisan Rasulullah SAW Membawa Kemuliaan Umat - Yalawae, Asming; Ibrahim, Ahmad Farid (Jurnal Usuluddin, 2007)
The article aims to discuss the concept of Islamic morality which forms an excellent heritage from the Prophet Muhammad s.a.w. for his Ummah in achieving dignities and honourables in this world and hereafter. It also discusses the role of this Islamic morality and its influence to humans life.